Comparative in silico analysis of SSRs in coding regions of high confidence predicted genes in Norway spruce (Picea abies) and Loblolly pine (Pinus taeda). Issue 1 (December 2015) - Ranade, Sonali; Lin, Yao-Cheng; Peer, Yves; García-Gil, María
Abstract Background Microsatellites or simple sequence repeats (SSRs) are DNA sequences consisting of 1–6 bp tandem repeat motifs present in the genome. SSRs are considered to be one of the most powerful tools in genetic studies. We carried out a comparative study of perfect SSR loci belonging to class I (≥20) and class II (≥12 and <20 bp) types located in coding regions of high confidence genes inPicea abies andPinus taeda . SSRLocator was used to retrieve SSRs from the full length CDS of predicted genes in both species. Results Trimers were the most abundant motifs in class I followed by hexamers inPicea abies, while trimers and hexamers were equally abundant inPinus taeda class I SSRs. Hexamers were most frequent within class II SSRs followed by trimers, in both species. Although the frequency of genes containing SSRs was slightly higher inPinus taeda, SSR counts per Mbp for class I was similar in both species (P -value = 0.22); while for class II SSRs, it was significantly higher inPicea abies (P -value = 0.00009). AT-rich motifs were higher in abundance than the GC-rich motifs, within class II SSRs in both the species (P -values = 10−9 and 0). With reference to class I SSRs, AT-rich and GC-rich motifs were detected with equal frequency inPinus taeda (P -value = 0.24); while inPicea abies, GC-rich motifs were detected with higher frequency than the AT-rich motifs (P -value = 0.0005). Conclusions Our study gives a comparative overview of the genome SSRs composition based on high confidence genes in the two recently sequenced and economically important conifers and, also provides information on functional molecular markers that can be applied in genetic studies inPinus andPicea species.